Water-based coating composition

By employing silica-coated aluminum powder with a specific inter-dipole force and matching solvent conditions, the challenge of unstable dispersion in water-based paints is addressed, achieving superior dispersion stability in aqueous coating compositions.

JP2025069526APending Publication Date: 2025-05-01NIPPON PAINT AUTOMOTIVE COATINGS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023179294
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

It is difficult to stably disperse aluminum powder in water-based paint compositions due to its reactivity with water and variations in dispersion stability.

Method used

The use of silica-coated aluminum powder with an apparent inter-dipole force (δpa) of 10.65 or more, combined with a solvent having an inter-dipole force (δps) of δpa+1.00 or less, to achieve stable dispersion in aqueous solvents.

Benefits of technology

This approach results in an aqueous coating composition with excellent dispersion stability of aluminum powder, ensuring consistent performance in water-based paint applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069526000001
    Figure 2025069526000001
  • Figure 2025069526000002
    Figure 2025069526000002
  • Figure 2025069526000003
    Figure 2025069526000003
Patent Text Reader

Abstract

To provide a water-based coating composition which contains aluminum powder and is excellent in dispersion stability.SOLUTION: A water-based coating composition contains a coating film forming resin, aluminum powder having a silicon-containing film, and a solvent containing water, wherein the aluminum powder having the silicon-containing film has δpa as an apparent inter-dipolar force determined by the following method, the δpa is 10.65 or more, and the inter-dipolar force of the solvent is δpa+1.00 or less. (Method for determining apparent inter-dipolar force of aluminum powder) The method charges 0.0005 g of the aluminum powder having the silicon-containing film into a reference solvent obtained by mixing pure water and methanol in a prescribed ratio, and measures a time required until all the aluminum powder having the silicon-containing film sinks. The largest inter-dipolar force of the reference solvent when the time is equal to or less 60 seconds is defined as an apparent inter-dipolar force (δpa) of the aluminum powder having the silicon-containing film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous coating composition. [Background technology]

[0002] In recent years, for environmental conservation, there has been a demand for reducing emissions of volatile organic compounds (VOCs) from factories, etc. As one method for reducing VOC emissions, water-based coating compositions have been proposed.

[0003] Aluminum powder, which is often used as a brilliant pigment, reacts with water, so it is usually blended into an aqueous paint composition after being surface-treated. In this regard, Patent Documents 1 and 2 disclose blending silica-coated aluminum powder into an aqueous paint. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-187246 A [Patent Document 2] JP 2016-188285 A [Non-patent literature]

[0005] [Non-Patent Document 1] Toshikatsu Kobayashi, "Measuring Affinity -Solubility Parameters-", Journal of the Japan Color Materials Association, Japan Color Materials Association, 77(4), 188-192 (2004) Summary of the Invention [Problem to be solved by the invention]

[0006] It is difficult to stably disperse aluminum powder in water. An object of the present invention is to provide an aqueous coating composition containing aluminum powder and having excellent dispersion stability. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides the following aspects. [1] A film-forming resin; an aluminum powder having a silicon-containing coating; a solvent comprising water, The aluminum powder having the silicon-containing coating has an apparent dipole-dipole force (δp value) of δpa determined by the following method, The Δpa is 10.65 or more, An aqueous coating composition, wherein the dipole-dipole force (δps) of the solvent is δpa+1.00 or less. (Method for determining the apparent dipole-dipole force (δpa) of aluminum powder) 0.0005 g of the aluminum powder having the silicic coating is poured into a reference solvent obtained by mixing pure water and methanol in a specified ratio, and the time taken for all of the aluminum powder having the silicic coating to sink is measured. When this time is 60 seconds or less, the largest dipole-dipole force (δp value) of the reference solvent is taken as the apparent dipole-dipole force (δpa) of the aluminum powder having the silicic coating. [2] The aqueous coating composition according to the above [1], wherein the dipole-dipole force (δps) of the solvent is 9.70 or more and 15.3 or less. [3] The aqueous coating composition according to the above item [1] or [2], wherein the mass ratio of the aluminum powder having the silicon-containing coating to the mass of the solid content of the resin of the aqueous coating composition is 0.1 mass% or more and 50 mass% or less. [4] The aqueous coating composition according to the above item [1] or [2], wherein the coating film-forming resin comprises an aqueous acrylic resin. Effect of the Invention

[0008] According to the present invention, there is provided an aqueous coating composition which contains aluminum powder and has excellent dispersion stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The aluminum powder to be incorporated in the aqueous coating composition is usually surface-treated to impart water resistance. For example, inorganic phosphorus compounds, molybdenum compounds, silicon compounds, or organic resins are used for the surface treatment of the aluminum powder. Among them, aluminum powder treated with silicon compounds has high water dispersibility. However, even aluminum powder having a silicon-containing coating (hereinafter referred to as silica-coated aluminum powder) has variation in dispersion stability.

[0010] The dispersion stability of a pigment is affected by the pigment's wettability with respect to the solvent. When a pigment wets a solvent, the cohesive force between the pigments decreases, and as a result, the pigments can be dispersed. A well-known method for evaluating wettability is to use the solubility parameter (SP value). The SP value is calculated from three forces: van der Waals force (δd), dipole-dipole force (δp), and hydrogen bond force (δh). The SP value can be expressed in a three-dimensional coordinate space (δd, δp, δh) with each of the above forces as its axis.

[0011] The SP value is an index of the solubility of a two-component solvent, but it has also been proposed to use the SP value as an index of the dispersibility of a pigment, for example, as in Non-Patent Document 1. In Non-Patent Document 1, a pigment is floated in a certain amount of water, and a water-miscible organic solvent such as acetone or methanol is dropped onto the pigment without directly contacting it. The SP value of the mixture of water and organic solvent when the pigment begins to settle is calculated using a specific formula as the volume average of the SP values ​​of water and organic solvent, and this is used as a measure of the hydrophilicity of the pigment surface. The larger the SP value calculated above as a measure of the hydrophilicity of the pigment surface, the easier it is to wet with water.

[0012] The smaller the difference between the SP values ​​of the two components, the greater the solubility of the two. It is believed that the closer the SP value of the pigment calculated by the above theory is to the SP value of the solvent, the better the pigment will wet with that solvent, and the further away it is from the SP value of the solvent, the less likely the pigment will wet with that solvent. However, silica-coated aluminum powder does not necessarily satisfy the above relationship. In other words, a certain silica-coated aluminum powder may not wet with a water-containing solvent (hereinafter sometimes referred to as an "aqueous solvent") having an SP value close to the above SP value of the silica-coated aluminum powder, but may wet with an aqueous solvent having an SP value farther away from the above SP value.

[0013] According to an analysis of the three elements (δd, δp, and δh) for calculating the SP value, as shown in Table 1, a solvent having a large SP value does not necessarily have a large δp value (dipole force). For example, the solvents from methylene chloride to ethylene glycol in Table 1 show no correlation between the SP value and the δp value. Although Table 1 lists various solvents in order from smallest to largest SP value, the δp values ​​of the solvents from methylene chloride to ethylene glycol do not necessarily increase in order.

[0014] [Table 1]

[0015] The wettability of silica-coated aluminum powder in aqueous solvents is dominated by the δp value of the silica-coated aluminum powder. In other words, it is believed that the dispersion stability of silica-coated aluminum powder in aqueous solvents is determined by the δp value, not the SP value. The reason for this is not clear, but it is believed to be because the surface condition of silica-coated aluminum powder is significantly different from that of other commonly used pigments (including untreated aluminum powder) due to its silicon-containing coating.

[0016] As a new index (apparent δp value: δpa) equivalent to the δp value of the silica-coated aluminum powder, pure water and methanol are mixed in various ratios to prepare reference solvents with theoretical (calculated) δp values ​​of 7.86 to 15.3, and the δp value of the reference solvent in which the silica-coated aluminum powder sinks is adopted. This method makes it possible to determine an index showing the solubility (hydrophilicity) of the silica-coated aluminum powder more simply. Known SP values ​​and δp values ​​can be used for each solvent.

[0017] (Method for determining apparent dipole-dipole force (δpa) of silica-coated aluminum powder) 0.0005g of silica-coated aluminum powder is poured into a reference solvent obtained by mixing pure water and methanol at a predetermined ratio, and the time taken for all the silica-coated aluminum powder to sink is measured. The largest dipole-dipole force (δp value) of the reference solvent when this time is 60 seconds or less is taken as an index (apparent δp value: δpa) corresponding to the dipole-dipole force (δp value) of the silica-coated aluminum powder. Table 2 shows the compositions of reference solvents A to J used to determine the apparent δp value, and the theoretical δp values ​​and SP values ​​of reference solvents A to J. The mixing ratio of pure water and methanol is determined so that the theoretical δp value of the reference solvent includes the δp value (11.58 to 15.3) of a general water-based paint composition. The mixing ratio of pure water and methanol is changed by 10 mass% or less.

[0018] The theoretical Δp values ​​of the reference solvents A to J can be calculated by multiplying the Δp values ​​of various known solvents (pure water and methanol in the above case) by the volume fraction of the solvent and summing them up. The same applies to the theoretical SP values.

[0019] [Table 2]

[0020] Silica-coated aluminum powder with an apparent δp value of δpa can be stably dispersed in an aqueous solvent having a δp value of δpa+1.00 or less. The δp value (δps) of the aqueous solvent contained in the aqueous coating composition can also be determined from a known value by specifying its type (and further, the mixing ratio).

[0021] For example, when a silica-coated aluminum powder is placed in reference solvents A to J, if it sinks within 60 seconds in reference solvents B to J but does not sink in reference solvent A, the apparent Δp value of the silica-coated aluminum powder is 14.37. This silica-coated aluminum powder can be stably dispersed in, for example, an aqueous solvent having a Δp value of 14.50 or less.

[0022] When the silica-coated aluminum powder has an apparent δp value (δpa) of 10.65 or more, it can be dispersed in a general aqueous coating composition. The apparent δp value (δpa) (which can also be said to be the type of silica-coated aluminum powder) can be appropriately set according to the δp value (δps) of the aqueous solvent contained in the aqueous coating composition. δpa and δps should satisfy the relationship δps≦δpa+1.00.

[0023] The closer δpa and δps are, the more the dispersion stability of the silica-coated aluminum powder can be improved. Even if δps is smaller than δpa, the dispersion stability of the silica-coated aluminum powder can be improved. δps may be δpa+0.50 or less, δpa+0.20 or less, δpa or less, or δpa-1.00 or less. δps may be δpa-3.00 or more.

[0024] The aqueous coating composition contains a solvent (aqueous solvent) containing water. The proportion of water in the aqueous solvent is 50% by mass or more, may be 60% by mass or more, may be 70% by mass or more, may be 80% by mass or more, may be 90% by mass or more, or may be 100% by mass.

[0025] Hereinafter, the weight average molecular weight and number average molecular weight are measured using polystyrene standards by the GPC (gel permeation chromatography) method.

[0026] The Tg may be calculated from the types and amounts of raw material monomers, or may be measured by differential scanning calorimetry (DSC).

[0027] The hydroxyl value and acid value are determined based on the solid content mass. The hydroxyl value and acid value can be measured by a known method described in JIS K 0070:1992. The hydroxyl value and acid value may be calculated from the blending amount of the unsaturated monomer in the raw material monomer of the target resin.

[0028] The PWC is calculated using the solid mass of the resins (film-forming resin and hardener) and the mass proportion of the pigment contained in the coating composition according to the following formula. PWC(%)=100×pigment mass / ((pigment mass)+(resin solid mass))

[0029] The average particle size is the 50% average particle size (D50) in the volume-based particle size distribution measured using a particle size distribution measuring device using a laser diffraction / scattering method.

[0030] [Water-based paint composition] The water-based coating composition comprises a silica-coated aluminum powder, a film-forming resin, and an aqueous solvent.

[0031] (Silica-coated aluminum powder) Silica-coated aluminum powder is aluminum powder covered with a coating containing silicon. The coating containing silicon suppresses the reaction between aluminum and water and improves dispersibility in aqueous solvents. The presence of the coating containing silicon can be confirmed by analysis using X-ray photoelectron spectroscopy (XPS).

[0032] Silica-coated aluminum powder is obtained by treating aluminum powder with a silicon compound. The silicon compound has a silicon atom and two or more alkoxy groups bonded to the silicon atom. The alkoxy group generates a silanol group together with the silicon atom through hydrolysis. The silanol group is adsorbed to the surface of the aluminum powder and bonds by hydrogen bonding. Furthermore, other silanol groups undergo dehydration condensation to oligomerize the silicon compound. As a result, the surface of the aluminum powder is covered with a coating containing silicon (silica coating).

[0033] Examples of silicon compounds include at least one of tetraalkoxysilane and so-called silane coupling agents. Examples of tetraalkoxysilane include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, and tetrabutoxysilane. These may be used alone or in combination of two or more.

[0034] Examples of the silane coupling agent include methyltrimethoxysilane, methyltriethoxysilane, methyltributoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldibutoxysilane, trimethylmethoxysilane, trimethylethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-propyltributoxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltributoxysilane, dibutyldimethoxysilane, dibutyldiethoxysilane, dibutyldibutoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, dihexyldimethoxysilane, Examples of the silane include dihexyldiethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, dioctyldimethoxysilane, dioctyldiethoxysilane, dioctylethoxybutoxysilane, decyltrimethoxysilane, decyltriethoxysilane, didecyldimethoxysilane, didecyldiethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, dioctadecyldimethoxysilane, dioctadecyldiethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, trifluoropropyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, and 3-chloropropyltributoxysilane. These may be used alone or in combination of two or more.

[0035] The thickness of the silica coating is, for example, 10 nm or more and 50 nm or less. The thickness of the silica coating may be 40 nm or less, or may be 30 nm or less.

[0036] The thickness of the silica coating is measured using a cross-section of the silica-coated aluminum powder photographed with a STEM (scanning transmission electron microscope). Using image analysis software, the shortest distances from any five points on the boundary between the metallic aluminum and the silica coating to the outer surface of the silica coating are measured and averaged on the cross-section of the silica-coated aluminum powder. This value is the thickness of the silica coating.

[0037] The average primary particle diameter D0 of the silica-coated aluminum powder is, for example, 1 μm or more and 40 μm or less. The average primary particle diameter D0 may be 3 μm or more, 4 μm or more, or 5 μm or more. The average primary particle diameter D0 may be 30 μm or less, 20 μm or less, or 15 μm or less.

[0038] The silica-coated aluminum powder is typically flaky. The thickness T of the scaly silica-coated aluminum powder is, for example, 20 nm or more and 1 μm or less. The thickness T may be 30 nm or more. The thickness T may be 300 nm or less. The aspect ratio (average primary particle size / thickness) of the scaly silica-coated aluminum powder is, for example, 20 or more and 1000 or less. The thickness T is also obtained by measuring and averaging the cross-sectional image of the silica-coated aluminum powder as described above.

[0039] Silica-coated aluminum powder with an apparent δp value (δpa) of 10.65 or more has excellent dispersion stability in an aqueous solvent with a δp value of δpa+1.00 or less. For example, when 250 g of an aqueous coating composition containing the aqueous solvent and silica-coated aluminum powder is diluted with 50 g of pure water and thoroughly stirred to prepare a diluted solution, the average particle diameter D1 of the silica-coated aluminum powder at the initial preparation stage (within 24 hours after the diluted solution is prepared) and the average particle diameter D2 of the silica-coated aluminum powder after 3 weeks of stirring the diluted solution are: D2≦D1×3.0 The relationship can be satisfied.

[0040] D1 and D2 may satisfy the relationship D2≦D1×2.5, may satisfy the relationship D2≦D1×2.0, or may satisfy the relationship D2≦D1×1.5.

[0041] The average primary particle diameter D0 of the silica-coated aluminum powder and the average particle diameter D1 of the silica-coated aluminum powder at the initial preparation stage can also satisfy the relationship D1≦D0×3.0. That is, the silica-coated aluminum powder has excellent dispersibility in a liquid containing an aqueous solvent that satisfies the relationship δps≦δpa+1.00. D0 and D1 can satisfy the relationship D1≦D0×2.5, D1≦D0×2.0, and D1≦D0×1.5.

[0042] The δpa of the silica-coated aluminum powder is 10.65 or more. The δpa of the silica-coated aluminum powder may be 11.0 or more. The δpa of the silica-coated aluminum powder may be, for example, 15.3 or less. The apparent SP value of the silica-coated aluminum powder is, for example, 19.0 or more and 23.4 or less.

[0043] The mass ratio (PWC) of the silica-coated aluminum powder to the resin solid content mass of the aqueous coating composition is, for example, 0.1 mass% or more and 50 mass% or less. The silica-coated aluminum powder exhibits good dispersion stability regardless of its blending amount. The PWC of the silica-coated aluminum powder may be 10 mass% or more, or 20 mass% or more. The PWC of the silica-coated aluminum powder may be 40 mass% or less, or 30 mass% or less.

[0044] (Coating film forming resin) Examples of the film-forming resin include acrylic resin, polyester resin, polyurethane resin, alkyd resin, fluororesin, epoxy resin, polyether resin, and polyol resin. These may be used alone or in combination of two or more. In the aqueous coating composition, the film-forming resin may be included as an emulsion, a dispersion, or dissolved in an aqueous solvent.

[0045] In particular, the aqueous coating composition may contain, as the film-forming resin, an aqueous acrylic resin, or may contain an aqueous acrylic resin and an aqueous polyurethane resin.

[0046] <Water-based acrylic resin> The aqueous acrylic resin may be in the form of an emulsion or may be water-dispersible. The acrylic resin emulsion may have a single-layer structure or a multi-layer structure including a core portion and a shell portion that covers at least a part of the surface of the core portion.

[0047] The hydroxyl value (OHV) of the aqueous acrylic resin is, for example, 20 mgKOH / g or more and 180 mgKOH / g or less. When the hydroxyl value of the aqueous acrylic resin is 20 mgKOH / g or more, the breaking strength of the coating film is likely to be high. When the hydroxyl value of the aqueous acrylic resin is 180 mgKOH / g or less, the hydrophilization of the coating film is suppressed, and the water resistance is likely to be improved. The hydroxyl value of the aqueous acrylic resin may be 30 mgKOH / g or more, or 40 mgKOH / g or more. The hydroxyl value of the aqueous acrylic resin may be 150 mgKOH / g or less, 140 mgKOH / g or less, or 120 mgKOH / g or less.

[0048] The glass transition temperature (Tg) of the aqueous acrylic resin is, for example, -20°C or higher and 100°C or lower. When the Tg of the aqueous acrylic resin is -20°C or higher, the breaking strength and hardness of the resulting coating film are likely to be improved. When the Tg of the aqueous acrylic resin is 100°C or lower, the quick-drying property of the aqueous coating composition is likely to be improved. The Tg of the aqueous acrylic resin may be -15°C or higher. The Tg of the aqueous acrylic resin may be 90°C or lower, 80°C or lower, 70°C or lower, or 50°C or lower.

[0049] The acid value (AV) of the aqueous acrylic resin is, for example, 5 mgKOH / g or more and 70 mgKOH / g or less. When the acid value of the aqueous acrylic resin is 5 mgKOH / g or more, the hardness of the resulting coating film is likely to be improved. When the acid value of the aqueous acrylic resin is 70 mgKOH / g or less, the water resistance of the resulting coating film can be improved. The acid value of the aqueous acrylic resin may be 7 mgKOH / g or more, or 10 mgKOH / g or more. The acid value of the aqueous acrylic resin may be 60 mgKOH / g or less, 50 mgKOH / g or less, or 40 mgKOH / g or less.

[0050] For example, the acrylic resin emulsion can be prepared by emulsion polymerization of α,β-ethylenically unsaturated monomers. Examples of the α,β-ethylenically unsaturated monomers include (meth)acrylic acid esters, α,β-ethylenically unsaturated monomers having an acid group, and α,β-ethylenically unsaturated monomers having a hydroxyl group. The monomers can be used alone or in combination of two or more.

[0051] Examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, and dihydrodicyclopentadienyl (meth)acrylate. (Meth)acrylic acid esters refer to acrylic acid esters and methacrylic acid esters.

[0052] Examples of α,β-ethylenically unsaturated monomers having an acid group include acrylic acid, methacrylic acid, crotonic acid, 2-acryloyloxyethyl phthalic acid, 2-acryloyloxyethyl succinic acid, ω-carboxy-polycaprolactone mono(meth)acrylate, isocrotonic acid, α-hydro-ω-((1-oxo-2-propenyl)oxy)poly(oxy(1-oxo-1,6-hexanediyl)), maleic acid, fumaric acid, itaconic acid, 3-vinylsalicylic acid, 3-vinylacetylsalicylic acid, 2-acrylamido-2-methylpropanesulfonic acid, p-hydroxystyrene, and 2,4-dihydroxy-4′-vinylbenzophenone.

[0053] Examples of the α,β-ethylenically unsaturated monomer having a hydroxyl group include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, allyl alcohol, methallyl alcohol, and adducts of these with ε-caprolactone.

[0054] Other α,β-ethylenically unsaturated monomers may be used in combination. Examples of other α,β-ethylenically unsaturated monomers include polymerizable amide compounds, polymerizable aromatic compounds, polymerizable nitriles, polymerizable alkylene oxide compounds, polyfunctional vinyl compounds, polymerizable amine compounds, α-olefins, dienes, polymerizable carbonyl compounds, polymerizable alkoxysilyl compounds, and other polymerizable compounds.

[0055] The method of emulsion polymerization is not particularly limited. For example, an emulsifier is dissolved in an aqueous medium containing water or, if necessary, an organic solvent such as alcohol, ether (e.g., dipropylene glycol methyl ether, propylene glycol methyl ether, etc.), and an α,β-ethylenically unsaturated monomer and a polymerization initiator are dropped under heating and stirring. The α,β-ethylenically unsaturated monomer may be emulsified in advance by an emulsifier.

[0056] The polymerization initiator and emulsifier may be those commonly used by those skilled in the art. If necessary, the molecular weight may be adjusted using a chain transfer agent such as mercaptan (e.g., lauryl mercaptan) and α-methylstyrene dimer. The reaction temperature, reaction time, etc. may be appropriately selected within the range commonly used by those skilled in the art. The obtained acrylic resin emulsion is neutralized with a base as necessary.

[0057] The average particle size of the acrylic resin emulsion may be, for example, 50 nm or more and 500 nm or less. When the average particle size of the acrylic resin emulsion is within the above range, the paint stability is improved and the smoothness of the resulting coating film is also improved. The average particle size of the acrylic resin emulsion may be 80 nm or more. The average particle size of the acrylic resin emulsion may be 300 nm or less.

[0058] The water-dispersible acrylic resin can be prepared, for example, by solution polymerization of a mixture of the above monomers.

[0059] The weight average molecular weight (Mw) of the water-dispersible acrylic resin is, for example, 4,000 or more and 50,000 or less. When the Mw of the water-dispersible acrylic resin is 4,000 or more, the hardness and weather resistance of the resulting coating film are likely to be improved. When the Mw of the water-dispersible acrylic resin is 50,000 or less, excessive viscosity increase of the aqueous coating composition is likely to be suppressed. The Mw of the water-dispersible acrylic resin may be 5,000 or more, or 8,000 or more. The Mw of the water-dispersible acrylic resin may be 40,000 or less, or 30,000 or less.

[0060] As the aqueous acrylic resin, an acrylic resin in an emulsion form (acrylic resin emulsion) and a water-dispersible acrylic resin may be used in combination. In this case, the ratio (We / Wd) of the solid content mass We of the acrylic resin emulsion to the solid content mass Ws of the water-dispersible acrylic resin is, for example, 1 or more and 15 or less. We / Wd may be 3 or more, or 5 or more. We / Wd may be 10 or less, or 8 or less.

[0061] The content of the aqueous acrylic resin is, for example, 10 parts by mass or more and 60 parts by mass or less, based on 100 parts by mass of the resin solid content of the aqueous coating composition. The content of the aqueous acrylic resin may be 20 parts by mass or more, or 30 parts by mass or more. The content of the aqueous acrylic resin may be 50 parts by mass or less.

[0062] <Water-based polyurethane resin> The aqueous polyurethane resin improves the chipping resistance of the resulting coating film. The aqueous polyurethane resin is typically water-dispersible.

[0063] The Tg of the aqueous polyurethane resin is, for example, −50° C. or lower. This can improve the chipping resistance and water resistance of the resulting coating film. The Tg of the aqueous polyurethane resin may be −55° C. or lower, or −58° C. or lower.

[0064] The polyurethane resin is obtained, for example, by reacting a polyol compound, a compound having an active hydrogen group and a hydrophilic group in the molecule, an organic polyisocyanate compound, and, if necessary, a chain extender and a polymerization terminator. If necessary, the chain extender and the polymerization terminator may be used.

[0065] The aqueous polyurethane resin can be obtained, for example, by a method of forcibly emulsifying the polyurethane resin using a surfactant, or by a method of neutralizing the polyurethane resin with a base or an acid.

[0066] The polyol compound contains two or more hydroxyl groups in the molecule. Examples of the polyol compound include polyhydric alcohols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, trimethylolpropane, and glycerin, polyether polyols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol, polyester polyols obtained from dicarboxylic acids such as adipic acid, sebacic acid, itaconic acid, maleic anhydride, phthalic acid, and isophthalic acid and glycols such as ethylene glycol, triethylene glycol, propylene glycol, butylene glycol, tripropylene glycol, and neopentyl glycol, polycaprolactone polyols, polybutadiene polyols, polycarbonate polyols, and polythioether polyols. These may be used alone or in combination of two or more.

[0067] Examples of compounds having active hydrogen groups and hydrophilic groups in the molecule include compounds containing active hydrogen and anionic, cationic or nonionic hydrophilic groups. The anionic groups include anionic groups and anion-forming groups. The anion-forming groups are groups that can react with a base to form an anionic group, and specifically, the anionic groups are formed by neutralizing with a base before, during or after the urethane reaction.

[0068] Compounds containing active hydrogen and anionic groups are described, for example, in JP-B-42-24192 and JP-B-55-41607, and specifically include α,α-dimethylolpropionic acid and α,α-dimethylolbutyric acid. Compounds having active hydrogen and cationic groups are described, for example, in JP-B-43-9076. Compounds having active hydrogen and nonionic hydrophilic groups are described, for example, in JP-B-48-41718, and specifically include polyethylene glycol and alkyl alcohol alkylene oxide adducts.

[0069] Examples of the organic polyisocyanate compound include aromatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, and araliphatic polyisocyanates.

[0070] The chain extender contains two or more active hydrogen groups in the molecule. Examples of the chain extender include low molecular weight polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, 3-methylpentanediol, 2-ethyl-1,3-hexanediol, and trimethylolpropane; polyamines such as ethylenediamine, hexamethylenediamine, diethylenetriamine, hydrazine, xylylenediamine, and isophoronediamine; and water. These may be used alone or in combination of two or more.

[0071] Examples of the polymerization terminator include compounds having one active hydrogen in the molecule (such as monoalcohols and monoamines) and monoisocyanate compounds.

[0072] The polyurethane resin may be synthesized by a one-shot method in which each component is reacted at once, or by a multi-stage method in which the components are reacted stepwise. In the multi-stage method, a part of the active hydrogen-containing compound (e.g., a polymer polyol) is reacted with an organic polyisocyanate compound to form an NCO-terminated prepolymer, and then the prepolymer is reacted with the remaining part of the active hydrogen-containing compound.

[0073] The content of the aqueous polyurethane resin may be, for example, 1 part by mass or more and 10 parts by mass or less, based on 100 parts by mass of the resin solid content of the aqueous coating composition. The content of the aqueous polyurethane resin may be 3 parts by mass or more. The content of the aqueous polyurethane resin may be 7 parts by mass or less.

[0074] Other resins The aqueous coating composition may further contain at least one of an aqueous polyester resin and a polyol resin as a film-forming resin.

[0075] Water-based polyester resin The water-based polyester resins are typically water-dispersible. The aqueous polyester resin may have, for example, an AV of 15 mgKOH / g or more and 100 mgKOH / g or less, an OHV of 10 mgKOH / g or more and 170 mgKOH / g or less, an Mn of 800 or more and 10,000 or less, and a Tg of -40°C or more and 50°C or less.

[0076] The aqueous polyester resin can be obtained, for example, by polycondensation (ester reaction) of a polyhydric alcohol and a polybasic acid or an anhydride thereof.

[0077] The polyhydric alcohol is not particularly limited, and examples thereof include ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, neopentyl glycol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, hydrogenated bisphenol A, hydroxyalkylated bisphenol A, 1,4-cyclohexanedimethanol, 2,2-dimethyl- Examples of such compounds include 3-hydroxypropyl-2,2-dimethyl-3-hydroxypropionate, 2,2,4-trimethyl-1,3-pentanediol, N,N-bis-(2-hydroxyethyl)dimethylhydantoin, polytetramethylene ether glycol, polycaprolactone polyol, glycerin, sorbitol, trimethylolethane, trimethylolpropane, trimethylolbutane, hexanetriol, pentaerythritol, dipentaerythritol, and tris-(hydroxyethyl)isocyanate. These compounds may be used alone or in combination of two or more.

[0078] The polybasic acid or its anhydride is not particularly limited, and examples thereof include phthalic acid, phthalic anhydride, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, methyltetrahydrophthalic acid, methyltetrahydrophthalic anhydride, hymic anhydride, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, isophthalic acid, terephthalic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, adipic acid, azelaic acid, sebacic acid, succinic acid, succinic anhydride, lactic acid, dodecenylsuccinic acid, dodecenylsuccinic anhydride, cyclohexane-1,4-dicarboxylic acid, and endo anhydride. These may be used alone or in combination of two or more.

[0079] The content of the aqueous polyester resin is, for example, 5 parts by mass or more and 30 parts by mass or less, based on 100 parts by mass of the resin solid content of the aqueous coating composition. The content of the aqueous polyester resin may be 10 parts by mass or more. The content of the aqueous polyester resin may be 20 parts by mass or less.

[0080] Polyol resin The polyol resin has two or more hydroxyl groups in one molecule. Examples of the polyol include polycarbonate polyol resin, polyether polyol resin, and polycaprolactone polyol resin.

[0081] The polyol resin may have, for example, an AV of 5 mgKOH / g or more and 70 mgKOH / g or less, an OHV of 20 mgKOH / g or more and 180 mgKOH / g or less, and a Tg of -20°C or more and 100°C or less.

[0082] The content of the polyol resin is, for example, 1 part by mass or more and 20 parts by mass or less, based on 100 parts by mass of the resin solid content of the aqueous coating composition. The content of the polyol resin may be 3 parts by mass or more. The content of the polyol resin may be 10 parts by mass or less.

[0083] Hardener The aqueous coating composition may contain a curing agent, which allows a coating film with high hardness to be obtained.

[0084] Examples of the curing agent include melamine resin, blocked isocyanate compound, epoxy compound, aziridine compound, carbodiimide compound, oxazoline compound, and metal ion. These are used alone or in combination of two or more. The aqueous coating composition may contain melamine resin as a curing agent.

[0085] The content of the curing agent may be, for example, 5 parts by mass or more and 50 parts by mass or less, based on 100 parts by mass of the resin solid content of the aqueous coating composition. The content of the curing agent may be 10 parts by mass or more. The content of the curing agent may be 40 parts by mass or less.

[0086] Melamine resin The melamine resin mainly reacts with the hydroxyl group of the coating film-forming resin to form a crosslinked structure. The melamine resin may be water-soluble or water-insoluble. The melamine resin has three nitrogen atoms N around a triazine ring (triazine nucleus). 1 ~N 3 Six substituents R 1 ~R 6 The structure in which -N 1 (R 1 )(R 2 ), -N 2 (R 3 )(R 4 ), -N 3 (R 5 )(R 6 The triazine ring has a planar structure and is rigid, which further improves the hardness of the resulting coating film.

[0087] Substituent R 1 ~R 6 are each independently a hydrogen atom, an alkyl ether group (-CH-OR 7 ) and the methylol group (-CHOH). 1 ~R 6 , R 7may each independently be an alkyl group having 1 to 8 carbon atoms or an alkyl group having 1 to 4 carbon atoms. The alkyl group may be linear or branched. The alkyl group may be a methyl group, an n-butyl group, or an isobutyl group.

[0088] The melamine resin is generally composed of a polynuclear compound in which a plurality of triazine rings are bonded to each other, but the melamine resin may be a mononuclear compound composed of one triazine ring.

[0089] The melamine resin may, for example, be a compound having a substituent R 1 ~R 6 Full alkyl type with only alkyl ether groups as the alkyl group; -N(-CH2-OR 7 )(-CH2OH) with methylol group; -N(-CH2-OR 7 )(H) imino group type; -N(-CH2-OR 7 )(-CH2OH) and -N(-CH2-OR 7 ) (H) is a methylol / imino group type.

[0090] The number average molecular weight of the melamine resin is, for example, 300 or more and 2000 or less. This allows the viscosity of the aqueous coating composition to be kept low. The number average molecular weight of the melamine resin may be 1500 or less, or 1300 or less. The number average molecular weight of the melamine resin may be 350 or more, or 400 or more.

[0091] (Other pigments) The aqueous coating composition may contain pigments other than the silica-coated aluminum powder. Examples of the other pigments include color pigments, extender pigments, and other luster pigments.

[0092] Examples of color pigments include organic color pigments such as azo chelate pigments, insoluble azo pigments, condensed azo pigments, diketopyrrolopyrrole pigments, benzimidazolone pigments, phthalocyanine pigments, indigo pigments, perinone pigments, perylene pigments, dioxane pigments, quinacridone pigments, isoindolinone pigments, and metal complex pigments; and inorganic color pigments such as yellow lead, yellow iron oxide, red iron oxide, carbon black, and titanium dioxide. These may be used alone or in combination of two or more.

[0093] Examples of the extender pigment include calcium carbonate, barium sulfate, clay and talc. These may be used alone or in combination of two or more.

[0094] The total PWC of the color pigment and the extender pigment may be, for example, 10% by mass or more and 60% by mass or less. The total PWC may be 15% by mass or more, or 20% by mass or more. The total PWC may be 50% by mass or less, or 40% by mass or less.

[0095] Examples of other luster pigments include mica pigments such as interference mica, white mica, and colored mica; graphite pigments; glass flake pigments; and metal pigments such as non-silica-coated aluminum, copper, zinc, iron, nickel, tin, aluminum oxide, chromium oxide, and alloys containing these. These may be used alone or in combination of two or more. The other luster pigments may be colored or uncolored.

[0096] The PWC of the other bright pigment may be, for example, 1% by mass or more and 20% by mass or less. The PWC of the other bright pigment may be 1.5% by mass or more, or 2% by mass or more. The PWC of the other bright pigment may be 15% by mass or less, or 10% by mass or less.

[0097] <Aqueous solvent> The aqueous solvent contains at least water. The theoretical δp value (δPs) of the aqueous solvent is, for example, 9.70 or more and 15.3 or less. The δPs of the aqueous solvent may be 11.0 or more, or 12.0 or more. The δPs of the aqueous solvent may be 14.0 or less, or 13.0 or less.

[0098] The aqueous solvent may further contain an organic solvent so that the theoretical δp value is in the above range. The theoretical δp value of the organic solvent that may be contained is, for example, 0.5 or more and 15.3 or less. The theoretical δp value of the organic solvent may be 12 or more, or 14 or more.

[0099] Examples of organic solvents include alcohol-based solvents such as methanol, ethanol, butanol, and propyl alcohol; ester-based solvents such as ethyl acetate, butyl acetate, isopropyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate; ether-based solvents such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, methyl methoxybutanol, ethoxypropanol, ethylene glycol isopropyl ether, ethylene glycol-t-butyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, methoxybutanol, and propylene glycol monobutyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon-based solvents such as Swazol, Shellsol, and mineral spirits; and aromatic solvents such as xylene, toluene, Solvesso-100 (S-100), and Solvesso-150 (S-150). These may be used alone or in combination of two or more.

[0100] (others) The aqueous coating composition may contain various additives as necessary, such as ultraviolet absorbers, antioxidants, defoamers, dispersants, viscosity agents, pinhole inhibitors, and surface conditioners.

[0101] [Multi-layer coating] The aqueous coating composition is applied to an object to be coated to form a metallic base coating film, which, together with other coating films, constitutes a multi-layer coating film.

[0102] In one embodiment, the multi-layer coating film comprises a primer coating film provided on an object to be coated, a metallic base coating film provided on the primer coating film, and a clear coating film provided on the metallic base coating film.

[0103] (subject to be coated) Examples of the material of the object to be coated include metal, plastic, and foam. In particular, the object may be a metal (particularly a casting), and may be a metal that can be electrocoated. Examples of such metals include iron, copper, aluminum, tin, zinc, and alloys containing these metals.

[0104] The shape of the substrate is not particularly limited, and may be flat or three-dimensional. Specific examples of the substrate include automobile bodies and parts thereof, such as passenger cars, trucks, motorcycles, and buses.

[0105] The metal substrate may be subjected to a chemical conversion treatment using a phosphoric acid-based chemical conversion treatment agent, a zirconium-based chemical conversion treatment agent, or the like, and may be subjected to an electrodeposition coating. The electrodeposition coating composition may be of the cationic type or the anionic type. The cationic electrodeposition coating composition can form a coating film having excellent corrosion resistance.

[0106] (Primer coating) The primer coating is interposed between the substrate and the metallic base coating. The primer coating makes the painted surface uniform, making it easier to suppress unevenness in the metallic base coating.

[0107] The thickness of the cured primer coating may be from 5 μm to 60 μm, from the viewpoint of smoothness and chipping resistance of the coated article.

[0108] The primer coating film is formed by a primer coating composition. The primer coating composition may be water-based or solvent-based. The primer coating composition may be water-based. The water-based primer coating composition contains, for example, the above-mentioned acrylic resin emulsion and melamine resin. The primer coating composition may further contain a pigment and various additives.

[0109] The solvent-based coating composition contains an organic solvent as a main solvent. In the solvent-based coating composition, the proportion of the organic solvent in the solvent is 50 mass % or more, may be 70 mass % or more, or may be 100 mass %.

[0110] (Metallic base coating) The metallic base coating film is formed from the aqueous coating composition according to the present disclosure.

[0111] The thickness of the base coating film is not particularly limited and may be appropriately set depending on the purpose. The thickness of the base coating film after curing may be 0.1 μm or more and 45 μm or less.

[0112] (Clear coating) The clear coating film improves the gloss of the coated article and prevents the pigment blended in the lower layer from falling off or popping out.

[0113] The thickness of the cured clear coating film may be 15 μm or more and 50 μm or less from the viewpoints of scratch resistance and smoothness.

[0114] The clear coating film is formed by a clear coating composition. The clear coating composition may be solvent-based, water-based, or powder-type. The solvent-based clear coating composition may contain an acrylic resin and / or a polyester resin as a coating film-forming resin, and an amino resin and / or an isocyanate as a curing agent, from the viewpoint of transparency or acid etching resistance. The solvent-based clear coating composition may also contain an acrylic resin and / or a polyester resin having a carboxylic acid and / or an epoxy group. The clear coating composition may contain the above-mentioned various pigments to the extent that the transparency is not impaired. The clear coating composition may contain various additives as necessary.

[0115] [Manufacturing method for multi-layer coating film] The multilayer coating film is produced, for example, by a method comprising the steps of applying a primer coating composition onto a substrate to form an uncured primer coating film, curing the uncured primer coating film, applying an aqueous coating composition according to the present disclosure to form an uncured metallic base coating film, curing the uncured metallic base coating film, applying a clear coating composition onto the metallic base coating film to form an uncured clear coating film, and curing the uncured clear coating film.

[0116] When the clear coating film is formed, the primer coating film and the metallic base coating film may be cured or uncured. From the viewpoints of productivity, adhesion and water resistance, each coating film may be laminated without curing (so-called wet-on-wet coating), and then these multiple uncured coating films may be cured simultaneously.

[0117] Wet-on-wet coating comprises the steps of applying a primer coating composition onto an object to be coated to form an uncured primer coating film, applying the aqueous coating composition according to the present disclosure onto the uncured primer coating film to form an uncured metallic base coating film, applying a clear coating composition onto the uncured metallic base coating film to form an uncured clear coating film, and curing the uncured primer coating film, the uncured metallic base coating film, and the uncured clear coating film all at once.

[0118] After the primer coating composition is applied, preheating may be performed before applying the aqueous coating composition according to the present disclosure. After the aqueous coating composition according to the present disclosure is applied, preheating may be performed before applying the clear coating composition. Preheating is performed, for example, by leaving the substrate at a temperature of 20°C to 25°C for 5 to 15 minutes, or by heating the substrate at a temperature of 50°C to 80°C for 30 seconds to 10 minutes.

[0119] Examples of the coating method include air spray coating, airless spray coating, electrostatic spray coating, multi-stage coating (preferably two-stage coating) using air electrostatic spray coating, and coating that combines air electrostatic spray coating with a rotary atomizer-type electrostatic coater.

[0120] Curing of each coating composition is carried out, for example, under conditions of a heating temperature of 80° C. to 180° C. (preferably 100° C. to 160° C.) and a heating time of 5 minutes to 60 minutes (preferably 10 minutes to 30 minutes). EXAMPLES

[0121] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are by weight unless otherwise specified.

[0122] [Production Example 1] Production of acrylic resin emulsion 633 parts of deionized water was added to a reaction vessel, and the mixture was heated to 80° C. while being stirred and mixed in a nitrogen stream. Next, a monomer mixture for the first stage consisting of 75.65 parts by mass of styrene (ST), 178.96 parts by mass of methyl methacrylate (MMA), 75.94 parts by mass of n-butyl acrylate (BA), 64.45 parts by mass of 2-ethylhexyl acrylate (2-EHA), and 105.00 parts by mass of hydroxyethyl methacrylate (HEMA), 25.00 parts by mass of Aqualon HS-10 (polyoxyethylene alkylpropenyl phenyl ether sulfate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 25.00 parts by mass of Adeka Reasoap NE-20 (α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxyoxyethylene, manufactured by Asahi Denka Co., Ltd.), and 400 parts by mass of deionized water, and an initiator solution consisting of 1.2 parts of ammonium persulfate and 500 parts by mass of deionized water were dropped into the reaction vessel in parallel over a period of 1.5 hours. After the dropwise addition was completed, the mixture was aged at the same temperature for 1 hour.

[0123] Further, at 80°C, a second stage monomer mixture of 53.65 parts by mass of styrene (ST), 178.96 parts by mass of methyl methacrylate (MMA), 75.94 parts by mass of n-butyl acrylate (BA), 64.45 parts by mass of 2-ethylhexyl acrylate (2-EHA), 105.00 parts by mass of hydroxyethyl methacrylate (HEMA), and 22 parts by mass of acrylic acid, a monomer emulsion of 10 parts of Aqualon HS-10 and 250 parts of deionized water, and an initiator solution of 3.0 parts of ammonium persulfate and 500 parts of deionized water were dropped into the reaction vessel in parallel over 1.5 hours. After the dropwise addition was completed, the mixture was aged at the same temperature for 2 hours.

[0124] The mixture was then cooled to 40°C and filtered through a 400 mesh filter, after which 100 parts of deionized water and 1.6 parts of dimethylaminoethanol were added to adjust the pH to 6.5, yielding an acrylic resin emulsion with an average particle size of 150 nm, a solids concentration of 35%, an acid value of 20 mgKOH / g, a hydroxyl value of 100 mgKOH / g, and a Tg of -10°C.

[0125] The number average molecular weight was measured using a GPC apparatus "HLC8220GPC" (trade name, manufactured by Tosoh Corporation) and four columns "Shodex KF-606M" and "Shodex KF-603" (both trade names, manufactured by Showa Denko K.K.), under the following conditions: mobile phase: tetrahydrofuran, measurement temperature: 40°C, flow rate: 0.6 cc / min, and detector: RI.

[0126] [Production Example 2] Production of water-based acrylic resin 23.89 parts of tripropylene glycol methyl ether and 16.11 parts of propylene glycol methyl ether were added to the reaction vessel, and the mixture was heated to 105°C while being mixed and stirred in a nitrogen stream. Next, a monomer mixture containing 13.1 parts of methyl methacrylate, 68.4 parts of ethyl acrylate, 11.6 parts of 2-hydroxyethyl methacrylate, and 6.9 parts of methacrylic acid was prepared, and an initiator solution consisting of 100 parts of the monomer mixture, 10.0 parts of tripropylene glycol methyl ether, and 1 part of tertiary butyl peroxy 2-ethylhexanoate was dropped into the reaction vessel in parallel over 3 hours. After the dropwise addition, the mixture was aged at the same temperature for 0.5 hours.

[0127] Further, an initiator solution consisting of 5.0 parts of tripropylene glycol methyl ether and 0.3 parts of tertiary butyl peroxy 2-ethylhexanoate was added dropwise to the reaction vessel over 0.5 hours. After the completion of the addition, the mixture was aged at the same temperature for 2 hours.

[0128] After 16.1 parts of the solvent was distilled off at 110°C under reduced pressure (70 torr) using a solvent remover, 204 parts of deionized water and 7.1 parts of dimethylaminoethanol were added to obtain an aqueous acrylic resin solution. The resulting aqueous acrylic resin solution had a solids concentration of 30%, an acid value of 40 mgKOH / g, a hydroxyl value of 50 mgKOH / g, and a viscosity of 140 poise (E-type viscometer, 1 rpm / 25°C).

[0129] Tg was measured using a differential scanning calorimeter (DSC220C) manufactured by Seiko Instruments (SII), Inc. The measurement conditions were as follows: sample amount 10 mg, temperature rise rate 10°C / min, and measurement temperature range from -20°C to 100°C.

[0130] The AV and OHV were calculated based on the acid value and hydroxyl value of the raw material monomers used.

[0131] [Production Example 3] Production of water-based polyester resin 25.6 parts of isophthalic acid, 22.8 parts of phthalic anhydride, 5.6 parts of adipic acid, 19.3 parts of trimethylolpropane, 26.7 parts of neopentyl glycol, 17.5 parts of ε-caprolactone and 0.1 parts of dibutyltin oxide were added to the reactor, and the mixture was heated to 170°C while being mixed and stirred. The reaction mixture was then heated to 220°C over 3 hours, and water generated by the condensation reaction was removed until the acid value reached 8. Next, 7.9 parts of trimellitic anhydride were added to the reactor, and the mixture was reacted at 150°C for 1 hour to obtain a polyester resin with an acid value of 40. The polyester resin was further cooled to 100°C, and then 11.2 parts of butyl cellosolve were added and stirred until it was uniform. The polyester resin was then cooled to 60°C, and then 98.8 parts of ion-exchanged water and 5.9 parts of dimethylethanolamine were added. This resulted in an aqueous polyester resin with a solid content of 50% by mass. The solid content of the aqueous polyester resin was AV 40 mg KOH / g, OHV 110 mg KOH / g, Mn 2870, and Tg -3°C.

[0132] [Example 1] 7.09 parts of acrylic resin emulsion of Production Example 1, 1.22 parts of water-based acrylic resin of Production Example 2, 2.25 parts of water-based polyester resin of Production Example 3, 0.78 parts of water-based polyurethane resin (manufactured by Nippon Paint Automotive Coatings, Tg: -80°C), 0.76 parts of polyol resin (Primepol PX-1000, manufactured by Sanyo Chemical Industries, Ltd.), 5.25 parts of melamine resin (Cymel 327, manufactured by Allnex, solid content 90%), 3.21 parts of dispersant (Noigen EA-207D, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 55%), 0.48 parts of viscosity agent (Viscarex HV-30, manufactured by BASF, solid content 30%), 0.73 parts of defoamer, 0.15 parts of surface conditioner, silica coating An aqueous coating composition was obtained by mixing 0.42 parts of aluminum (WP-B5090P, manufactured by Asahi Kasei Corporation, δpa: 15.3), 3.58 parts of coloring pigment, 0.75 parts of extender pigment, 1.32 parts of other luster pigment, and 12.3 parts of an organic solvent (containing EHG (manufactured by Shoei Chemical Co., Ltd.) and 2EHOH (manufactured by Shoei Chemical Co., Ltd.) in a ratio of 5:2) and diluting the mixture with pure water to a total volume of 100 parts.

[0133] The apparent Δp value (ΔPa) and SP value of the silica-coated aluminum powder were determined based on the theoretical Δp values ​​or SP values ​​of the reference solvents A to J, respectively, as described above.

[0134] [Example 2, Comparative Examples 1-2] Except for changing the type of silica-coated aluminum as shown in Table 3, the same procedure as in Example 1 was followed to prepare aqueous coating compositions.

[0135] [Evaluation] Dispersion stability of silica-coated aluminum powder 250 g of the aqueous coating composition was diluted with 50 g of pure water and thoroughly stirred to prepare a diluted solution. After preparation of the diluted solution, the initial (24 hours) average particle diameter D1 of the silica-coated aluminum powder in the diluted solution and the average particle diameter D2 of the silica-coated aluminum powder in the diluted solution after 3 weeks of stirring were measured using a laser diffraction / scattering particle size distribution measuring device. The evaluation results are shown in Table 3.

[0136] [Table 3]

[0137] The present disclosure includes the following aspects. [1] A film-forming resin; an aluminum powder having a silicon-containing coating; a solvent comprising water, The aluminum powder having the silicon-containing coating has an apparent dipole-dipole force δpa determined by the following method: The Δpa is 10.65 or more, An aqueous coating composition, wherein the dipole-dipole force of the solvent is δpa+1.00 or less. (Method for determining the apparent dipole-dipole force of aluminum powder) 0.0005 g of the aluminum powder having the silicic coating is poured into a reference solvent obtained by mixing pure water and methanol in a specified ratio, and the time taken for all of the aluminum powder having the silicic coating to sink is measured. When this time is 60 seconds or less, the largest dipole-dipole force of the reference solvent is taken as the apparent dipole-dipole force (δpa) of the aluminum powder having the silicic coating. [2] The aqueous coating composition according to [1] above, wherein the dipole-dipole force of the solvent is 9.70 or more and 15.3 or less. [3] The aqueous coating composition of [1] or [2] above, wherein the mass ratio of the aluminum powder having the silicon-containing coating to the mass of the solid content of the resin of the aqueous coating composition is 0.1 mass % or more and 50 mass % or less. [4] The aqueous coating composition according to any one of the above [1] to [3], wherein the coating film-forming resin comprises an aqueous acrylic resin. [Industrial Applicability]

[0138] According to the present invention, there is provided an aqueous coating composition containing an aluminum powder having excellent dispersion stability. The aqueous coating composition of the present invention is particularly suitable for painting automobiles.

Claims

1. A film-forming resin; an aluminum powder having a silicon-containing coating; a solvent comprising water, The aluminum powder having the silicon-containing coating has an apparent dipole-dipole force δp determined by the following method: The δpa is 10.65 or more, An aqueous coating composition, wherein the dipole-dipole force of the solvent is δpa+1.00 or less. (Method of determining the apparent dipole force of aluminum powder) 0.0005 g of the aluminum powder having the silicic coating is poured into a reference solvent obtained by mixing pure water and methanol in a specified ratio, and the time taken for all of the aluminum powder having the silicic coating to sink is measured. When this time is 60 seconds or less, the largest dipole-dipole force of the reference solvent is taken as the apparent dipole-dipole force (δpa) of the aluminum powder having the silicic coating.

2. 2. The aqueous coating composition according to claim 1, wherein the dipole-dipole force of the solvent is 9.70 or more and 15.3 or less.

3. 3. The aqueous coating composition according to claim 1, wherein the mass ratio of the aluminum powder having the silicon-containing coating to the mass of the solid content of the resin of the aqueous coating composition is 0.1 mass % or more and 50 mass % or less.

4. 3. The aqueous coating composition according to claim 1, wherein the film-forming resin comprises an aqueous acrylic resin.

Citation Information

Patent Citations

  • Water-based metallic coating composition, and coated body

    JP2020007399A

  • Aqueous coloring base coating composition and repair coating method using the same

    JP2015187246A

  • Aqueous metallic base coating composition

    JP2016188285A